The role of demethylase AlkB homologs in cancer - Li, Qiao; Zhu, Qingsan (Frontiers in Oncology, 2023)
The AlkB family (ALKBH1-8 and FTO), a member of the Fe (II)- and α-ketoglutarate-dependent dioxygenase superfamily, has shown the ability to catalyze the demethylation of a variety of substrates, including DNA, RNA, and histones. Methylation is one of the natural organisms' most prevalent forms of epigenetic modifications. Methylation and demethylation processes on genetic material regulate gene transcription and expression. A wide variety of enzymes are involved in these processes. The methylation levels of DNA, RNA, and histones are highly conserved. Stable methylation levels at different stages can coordinate the regulation of gene expression, DNA repair, and DNA replication. Dynamic methylation changes are essential for the abilities of cell growth, differentiation, and division. In some malignancies, the methylation of DNA, RNA, and histones is frequently altered. To date, nine AlkB homologs as demethylases have been identified in numerous cancers' biological processes. In this review, we summarize the latest advances in the research of the structures, enzymatic activities, and substrates of the AlkB homologs and the role of these nine homologs as demethylases in cancer genesis, progression, metastasis, and invasion. We provide some new directions for the AlkB homologs in cancer research. In addition, the AlkB family is expected to be a new target for tumor diagnosis and treatment.